Antibiotic Overuse at Discharge in Hospitalized Patients with Bacteriuria or Treated for Pneumonia: A Multihospital Study. (October 2020) - Vaughn, Valerie M; Petty, Lindsay A.; Gandhi, Tejal N.; Kaye, Keith S.; Malani, Anurag; Bernstein, Steven J.; Ratz, David; McLaughlin, Elizabeth; Flanders, Scott A.
Abstract : Background: Nearly half of hospitalized patients with bacteriuria or treated for pneumonia receive unnecessary antibiotics (noninfectious or nonbacterial syndrome such as asymptomatic bacteriuria), excess duration (antibiotics prescribed for longer than necessary), or avoidable fluoroquinolones (safer alternative available) at hospital discharge. 1–3 However, whether antibiotic overuse at discharge varies between hospitals or is associated with patient outcomes remains unknown. Methods: From July 2017 to December 2018, trained abstractors at 46 Michigan hospitals collected detailed data on a sample of adult, non–intensive care, hospitalized patients with bacteriuria (positive urine culture with or without symptoms) or treated for community-acquired pneumonia (CAP; includes those with the disease formerly known as healthcare-associated pneumonia [HCAP]). Antibiotic prescriptions at discharge were assessed for antibiotic overuse using a previously described, guideline-based hierarchical algorithm. 3 Here, we report the proportion of patients discharged with antibiotic overuse by the hospital. We also assessed hospital-level correlation (using Pearson's correlation coefficient) between antibiotic overuse at discharge for patients with bacteriuria and patients treated for CAP. Finally, we assessed the association of antibiotic overuse at discharge with patient outcomes (mortality, readmission, emergency department visit, and antibiotic-associated adverse events) at 30 days using logit generalized estimating equations adjusted for patient characteristics and probability of treatment. Results: Of 17, 081 patients (7, 207 with bacteriuria; 9, 874 treated for pneumonia), nearly half (42.2%) had antibiotic overuse at discharge (36.3% bacteriuria and 51.1% pneumonia). The percentage of patients discharged with antibiotic overuse varied 5-fold among hospitals from 14.7% (95% CI, 8.0%–25.3%) to 74.3% (95% CI, 64.2%–83.8%). Hospital rates of antibiotic overuse at discharge were strongly correlated between bacteriuria and CAP (Pearson's correlation coefficient, 0.76; P ≤ .001) (Fig. 1). In adjusted analyses, antibiotic overuse at discharge was not associated with death, readmission, emergency department visit, or Clostridioides difficile infection. However, each day of overuse was associated with a 5% increase in the odds of patient-reported antibiotic-associated adverse events after discharge (Fig. 2). Conclusions: Antibiotic overuse at discharge was common, varied widely between hospitals, and was associated with patient harm. Furthermore, antibiotic overuse at discharge was strongly correlated between 2 disparate diseases, suggesting that prescribing culture or discharge processes—rather than disease-specific factors—contribute to overprescribing at discharge. Thus, discharge stewardship may be needed to target multiple diseases. Funding: This study was supported by the Society for Healthcare Epidemiology of America and by Blue Cross Blue Shield of Michigan and Blue Care Network. Disclosures: Valerie M. Vaughn reports contracted research for Blue Cross and Blue Shield of Michigan, the Department of VA, the NIH, the SHEA, and the APIC. She also reports receipt of funds from the Gordon and Betty Moore Foundation Speaker's Bureau, the CDC, the Pew Research Trust, Sepsis Alliance, and the Hospital and Health System Association of Pennsylvania.